Nursing Care for Pregnant Women with Hypovelemia Due to Hyperemesis Gravidarum Using Zingiber Officinale Herbal Therapy - Ni Luh Putu Lia Kristina; Putu Indah Sintya Dewi; Ni Putu Diah Ayu Rusmeni (STIKes Budi Luhur Cimahi, 2025)
Hyperemesis gravidarum is a condition characterized by excessive vomiting, which may lead to dehydration, electrolyte imbalance, acid-base disturbances, and significant weight loss in pregnant women. Management of hyperemesis gravidarum requires controlling nausea and vomiting to prevent active fluid loss. One potential complementary intervention is the use of Zingiber officinale (ginger) herbal therapy.This study aims to describe complementary nursing care focused on managing hypovolemia in a patient with hyperemesis gravidarum through the use of Zingiber officinale herbal therapy. The research employed a descriptive case study design to identify nursing care problems in a patient diagnosed with hyperemesis gravidarum. The subject was Mrs. S, a G1P0A0H0 patient at 9 weeks of gestation. The identified nursing diagnosis was hypovolemia related to active fluid loss, evidenced by nausea and vomiting more than five times per day, weakness, dizziness, dry lip mucosa, capillary refill time (CRT) > 2 seconds, urine ketones 3+, and decreased blood pressure (100/60 mmHg). The nursing intervention focused on managing hypovolemia and reducing nausea and vomiting through the administration of Zingiber officinale herbal therapy twice daily. After 72 hours (3×24 hours) of nursing care, the evaluation showed improvement in the patient’s condition: no more vomiting or dizziness, CRT < 2 seconds, moist mucous membranes, negative urine ketones, improved fluid intake, and stable blood pressure (110/70 mmHg). This study concludes that Zingiber officinale herbal therapy is effective in reducing nausea and vomiting and may help prevent potential complications during pregnancy.